Dual-pressed chromium alloy hard alloy blade

By using powders of different WC average grain sizes in different intervals of cemented carbide blades and adding chromium, the problem of offsetting properties in the prior art is solved, and the mechanical properties difference and wear resistance of the blades are maintained.

CN119156264APending Publication Date: 2024-12-17SANDVIK MINING & CONSTR TOOLS AB
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380038530.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-09
Filing Date
2023-05-04
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing dual pressing methods are difficult to maintain the required differences in mechanical properties between different parts of the cemented carbide blade, resulting in differences in hardness and toughness being offset by grain size migration of the bonded phase.

Method used

By using powders of different WC average grain sizes in different intervals of the blade and adding an appropriate amount of chromium to the bonding phase, the adhesive does not migrate during the sintering process, thereby maintaining the original powder properties of each zone and forming a relatively small amount of chromium. Blades in hard and tougher zones.

Benefits of technology

The difference in required mechanical properties is achieved in different areas of the blade, improving the wear resistance and working life of the blade, while increasing the apparent hardness without reducing toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156264A_ABST
    Figure CN119156264A_ABST
Patent Text Reader

Abstract

A sintered cemented carbide insert for mining or cutting applications, the sintered cemented carbide insert comprising: a first zone comprising: 3-18% by weight of a binding phase; inevitable impurities; the average grain size of the tungsten carbide ranges from 0.5 mu m to 20 mu m. And a second zone comprising: a binding phase in the same amount (within + / -3 wt%) as the first zone; any unavoidable impurity; the average grain size of the tungsten carbide ranges from 0.5 mu m to 20 mu m. Wherein the first zone and the second zone (6) are adjacent to each other; wherein the WC average grain size in the first region is different from the WC average grain size in the second region; and the binding phases in both the first zone and the second zone comprise between 2 and 15% by weight of Cr, measured as a fraction of the total binder content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cemented carbide insert for mining or cutting applications manufactured by double pressing. Background Art

[0002] Cemented carbide has a unique combination of high elastic modulus, high hardness, high compressive strength, high wear resistance and good toughness level. Therefore, cemented carbide is often used in products such as mining and cutting inserts. Cemented carbide contains a hard ceramic (carbide) phase and a binder phase.

[0003] Typically, a single powder grade is pressed to form a mining or cutting insert, resulting in uniform material properties throughout the insert. However, it is often desirable to have different material properties in different parts of the insert. For example, it may be desirable to have one set of mechanical properties in a zone, such as at the working surface, and a different set of mechanical properties in a second zone, such as in the body of the insert, in order to optimize the life and performance of the insert. Therefore, attempts have previously been made to use a dual pressing process, using powders of different compositions in different parts of the green body, with the goal of producing a sintered body with different mechanical properties in different parts of the body.

[0004] However, this will generally fail to produce the desired differences in mechanical or other properties between different parts of the sintered body because, all other things being equal, during sintering the binder phase will migrate from the larger grain size regions to the smaller grain size regions, thereby offsetting any differences in hardness and toughness achieved by the different grain sizes.

[0005] Therefore, the problem to be solved is how to provide a blade having a harder region and a tougher region using a dual pressing process.

[0006] definition

[0007] “Cemented carbide” in this context means a material comprising at least 50 wt. % WC, possible other hard components common in the art of producing cemented carbide, and a metallic binder phase of one or more preferably selected from Fe, Co and Ni.

[0008] The term "green body" refers to a cemented carbide article manufactured by grinding one or more hard phase components and a binder together, making a powder thereof, and then pressing the powder to form a cemented carbide compact that has not yet been sintered. Summary of the invention

[0009] According to a first aspect of the present invention, there is a sintered cemented carbide insert for mining or cutting applications, the sintered cemented carbide insert comprising: a first zone, the first zone comprising: 3-18 wt. % binder phase; any unavoidable impurities; the balance tungsten carbide with an average grain size between 0.5-20 μm; and a second zone, the second zone comprising: the same amount of binder phase as the first zone (within + / - 3 wt. %); any unavoidable impurities; the balance tungsten carbide with an average grain size between 0.5-20 μm; wherein the first zone and the second zone are adjacent to each other; wherein the WC average grain size in the first zone is different from the WC average grain size in the second zone; characterized in that: the binder phase in both the first zone and the second zone comprises Cr between 2-15 wt. % measured as a fraction of the total binder content.

[0010] Advantageously, the presence of chromium in both the first zone and the second zone prevents cobalt from migrating from the zone with a larger WC average grain size to the zone with a smaller WC average grain size. This results in the original properties of the powder grade used in each different zone being maintained, thereby maintaining the properties required for the application. If too much Cr is added, the mechanical properties of the material may deteriorate. If there is not enough Cr, migration of the binder will occur between the different zones.

[0011] In addition, the presence of chromium improves the plastic deformation of the cemented carbide, which enables higher compressive stresses to be introduced into the cemented carbide when it is treated with a surface tumbling treatment such as tumbling. This increase in compressive stress provides an increase in apparent hardness, which improves the wear resistance of the cemented carbide without reducing toughness.

[0012] Another aspect of the present invention relates to a method for manufacturing a cemented carbide insert, the method comprising the following steps:

[0013] a) providing a first powder comprising between 3-18 wt% binder, 2-15 wt% Cr measured as a fraction of the total binder content, and any unavoidable impurities, and the balance a WC hard phase having a grain size of 0.5-20 μm;

[0014] b) pre-pressing the first powder to provide a first portion of a green body;

[0015] c) providing a second powder, the second powder comprising between 3-18 wt % of a binder, 2-15 wt % of Cr and any unavoidable impurities, and the balance of a WC hard phase having a grain size of 1-20 μm;

[0016] d) pressing the second powder onto the first portion of the green body to provide a second portion of the green body;

[0017] c) sintering the entire green compact to form the sintered cemented carbide insert having the first region and the second region.

[0018] Advantageously, this method produces a blade in which the original properties of the powder are maintained after sintering, thus enabling the production of a product having different desired material properties in different areas of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 : Schematic diagram of a blade with a straight interface.

[0020] Figure 2 : Schematic illustration of the insert with dome interface.

[0021] Figure 3 : Hardness distribution of the samples of the present invention.

[0022] Figure 4 : Graph of the cobalt content of samples of the invention.

[0023] Figure 5 : Compare the hardness distribution of samples.

[0024] Figure 6 : Diagram comparing the cobalt content of samples.

[0025] Figure 7 : Compare the hardness distribution of samples.

[0026] Figure 8 : Diagram comparing the cobalt content of samples. DETAILED DESCRIPTION

[0027] Figure 1 A sintered cemented carbide insert 2 for mining or cutting applications is shown: the sintered cemented carbide insert comprises: a first zone 4, the first zone comprising: 3-18 wt. % of a binder phase; any unavoidable impurities; the balance tungsten carbide having an average grain size between 0.5-20 μm; and a second zone 6, the second zone comprising: the same amount of binder phase as the first zone (within + / - 3 wt. %); any unavoidable impurities; the balance tungsten carbide having an average grain size between 0.5-20 μm; wherein the first zone 4 and the second zone 6 are adjacent to each other; wherein the WC average grain size in the first zone 4 is different from the WC average grain size in the second zone; characterised in that: the binder phase in both the first zone 4 and the second zone 6 comprises between 2-15 wt. % Cr measured as a fraction of the total binder content.

[0028] Preferably, the binder phase in both the first zone 4 and the second zone 6 comprises 3-10 wt.% Cr measured as a fraction of the total binder content. The chromium content in the binder phase in the first zone 4 and the second zone 6 may be the same or different.

[0029] Preferably, the content of the binder phase in the first region 4 and the second region 6 is between 4 and 15% by weight.

[0030] Preferably, the average WC grain size in each of the first region 4 and the second region 6 is between 1.0 and 16 μm.

[0031] Preferably, the binder phase comprises at least 80 wt % of one or more of cobalt, nickel, iron or a combination thereof.

[0032] Preferably, the binder phase comprises Co and / or Ni alloyed with chromium, most preferably Co, even more preferably between 3 and 20 wt. % Co. Optionally, the binder is a nickel-chromium or nickel-aluminum alloy alloyed with chromium.

[0033] To a large extent, the Cr dissolves into the binder phase, however a certain amount (eg, up to 3 mass %) of undissolved chromium carbides may be present in the cemented carbide body.

[0034] The region having a larger WC average grain size may be the first region 4 or the second region 5 .

[0035] The WC average grain size was estimated using the Jeffries method according to “The determination of grain size in metals”, Z. Jeffries, AH Kline, EB Zimmer, Transactions of the AIME, Vol. 54, pp. 594-607, 1916; “Grain-size measurements in metals, and importance of such information”, Z. Jeffries, Transactions of the Faraday Society, Vol. 12, pp. 40-56, 1916; and “Grain-size measurements”, Z. Jeffries, Metallurgical and Chemical Engineering, Vol. 18, p. 185, 1918.

[0036] In one embodiment, one or more cemented carbides selected from TiC, TaC and / or NbC are present in the first region 4 and / or the second region 6. For example, the first region and / or the second region may contain between 0.2-6 wt. % TiC, TaC and / or NbC.

[0037] In one embodiment, the difference in average grain size between the first zone 4 and the second zone 6 is >0.5 μm. If the difference in average grain size is too small, no hardness and toughness gradient will be generated. Preferably, the difference in average grain size between the first zone 4 and the second zone 6 is >1 μm, more preferably >2 μm, even more preferably >3 μm, even more preferably >4 μm, even more preferably >5 μm. In one embodiment, the difference in average grain size between the first zone 4 and the second zone 6 is between 0.5-14 μm.

[0038] In one embodiment, the difference between the binder phase content in the first region 4 and the second region 6 is less than 1.5 wt%, preferably <1.2 wt%. Advantageously, a lower difference in Co content results in less Co diffusion upon sintering.

[0039] In another embodiment, the content of the binder phase in the first region 4 and the second region 6 is the same.

[0040] In one embodiment, if Figure 1 As shown, the blade comprises a base 8, a working tip 10, a core 12 and a longitudinal central axis 14. However, it will be appreciated that the blade 2 may have a different form.

[0041] In one embodiment, if Figure 1 As shown, the first zone 4 is positioned at the base 8 , and the second zone 6 is positioned at the working tip 10 .

[0042] Figure 2 It is shown that, alternatively, the first zone 4 is positioned at the working top 10 and the second zone is positioned at the base 8 .

[0043] In one embodiment, the first region 4 may have a smaller WC average grain size than the second region 6. Alternatively, the first region 4 may have a larger WC average grain size than the second region 6.

[0044] In one embodiment, the first region 4 has a WC average grain size between 1-2 μm and the second region 6 has a WC average grain size between 3-16 μm. Advantageously, this provides an insert having a harder working tip and a tougher base or core, which will result in an increased working life of the insert.

[0045] Alternatively, the first region 4 has a WC average grain size between 3-16 μm and the second region 6 has a WC average grain size between 1-2 μm.

[0046] In one embodiment, the difference in hardness between the first zone 4 and the second zone 6 is >50 HV20, preferably >70 HV20. Advantageously, this provides a blade with a harder zone and a tougher zone, which increases the working life of the blade. The hardness of the cemented carbide blade is measured using the Vickers hardness measurement. The cemented carbide body is sectioned along the longitudinal axis and polished using a standard procedure. The hardness is measured according to ISO EN6507 3:2005.

[0047] In one embodiment, if Figure 1 As shown, the interface 16 between the first region 4 and the second region 6 is substantially straight. Advantageously, this facilitates manufacture.

[0048] In one embodiment, if Figure 2 As shown, the interface 16 between the first zone 4 and the second zone 6 is dome-shaped. Advantageously, this enables a more wear-resistant working surface to be formed.

[0049] The interface 16 may be of any other geometric shape suitable for the product, and any geometric shape of the interface 16 may be combined with any arrangement of the first area 4 and the second area 6 .

[0050] In one embodiment of the present invention, the cemented carbide in the first zone 4 and / or the second zone 6 comprises M7C3 carbides and / or M 23 C6 carbides, and may also contain M3C2 carbides, where M is Cr and may contain one or more of W, Co and any other elements added to the cemented carbide. This means in this context that M7C3 and / or M 23 C6 carbides should be clearly visible in SEM (scanning electron microscope) images using backscattering at a magnification large enough to detect particles with a size of 100 nm. In one embodiment of the present invention, the cemented carbide comprises an amount of (volume %) C7C3 carbides and / or C6 carbides. 23 C6 carbide) / volume % Co ratio given by M7C3 carbide and / or M 23 Suitably, the volume % (M7C3 carbide and / or M 23 The ratio of M7C3 carbide and / or M 23 The volume % of C6 carbides and Co binder can be measured by EBSD or image analysis using appropriate software.

[0051] In one embodiment, the cemented carbide in the first zone 4 and / or the second zone 6 is free of η phase and graphite. If the binder phase is composed of cobalt, the cemented carbide will be free of η phase and graphite when the Com / Co ratio is 0.75≤Com / Co≤0.98. Metals used as binder phases in cemented carbides, such as Co, Ni and Fe, are ferromagnetic. The saturation magnetization is the maximum possible magnetization of a ferromagnetic material, characterized in that all magnetic moments inside the material are oriented parallel. FoersterKOERZIMAT 1.096 is used to determine the magnetic saturation (Com) dipole moment jS of the insert and the derived weight ratio saturation magnetization σS (4πσ). The Co content is then measured using XRF (X-ray fluorescence) using a Malvern Panalytical Axios Max Advanced instrument. The Com / %Co range between η phase and graphite formation is affected by changing the binder composition, such as by adding Cr, Fe, Ni, etc.

[0052] The solubility of W in the binder phase is directly related to the carbon content. As the carbon content decreases, the amount of W in the binder increases until the limit of η phase formation is reached. If the carbon content is reduced to a lower level, the solubility of W in the binder will not increase further. In some cemented carbide grades that are beneficial to achieving a large amount of W dissolved in the binder, the carbon content remains low, but exceeds the limit of η phase formation.

[0053] In another embodiment of the present invention, the cemented carbide substrate in the first zone 4 and / or the second zone 6 comprises an η phase, and the η phase comprises Me12C and / or Me6C carbides, wherein Me is one or more metals selected from W, Mo and a binder phase metal. The Com / Co ratio of the cemented carbide is ≤0.69. If other ingredients, such as grain growth inhibitors, γ phase formers, etc., are added to the cemented carbide, the Com / Co ratio will be affected. However, the formed η phase is not present in the form of large agglomerates. Generally, the η phase is considered to be unnecessary in cemented carbide because it is traditionally present in large agglomerates of η phase grains, which are brittle and harmful to the properties of the cemented carbide. The cemented carbide according to this embodiment of the present invention should have a uniformly distributed η phase, which means in this article that the cemented carbide does not contain large agglomerates. The amount of η phase is at least 2 volume %, preferably at least 4 volume %. By selecting a range of substoichiometric carbon content as in the cemented carbide of this embodiment to provide a non-agglomerated η phase, the cemented carbide exhibits good properties. The η phase is present in the microstructure as a finely dispersed phase. Common carbides of the η phase are W6Co6C, W3Co3C, W6Ni6C, W3Ni3C, W6Fe6C, W3Fe3C. In one embodiment, the η phase contains both Me12C and Me6C.

[0054] In one embodiment, the insert comprises more than two zones, each of the zones having a different WC average grain size.

[0055] Another aspect of the present invention relates to a method for manufacturing a cemented carbide insert, the method comprising the following steps:

[0056] a) providing a first powder comprising between 3-18 wt% binder, 2-15 wt% Cr measured as a fraction of the total binder content, and any unavoidable impurities, and the balance a WC hard phase having a grain size of 0.5-20 μm;

[0057] b) pre-pressing the first powder to provide a first portion of a green body;

[0058] c) providing a second powder, the second powder comprising between 3-18 wt % of a binder, 2-15 wt % of Cr and any unavoidable impurities, and the balance of a WC hard phase having a grain size of 0.5-20 μm;

[0059] d) pressing the second powder onto the first portion of the green body to provide a second portion of the green body;

[0060] c) sintering the entire green compact to form the sintered cemented carbide insert having the first region 4 and the second region 6.

[0061] Cr is usually added to the powder blend in the form of Cr3C2 as this provides the highest proportion of Cr per gram of powder, but it will be appreciated that alternative chromium carbides such as Cr 26 C2 or Cr7C3 or chromium nitride or even chromium oxide is added to the powder blend.

[0062] In one embodiment, after sintering, the cemented carbide insert 2 is tumbled. Advantageously, tumbling introduces compressive stresses into the insert 2.

[0063] To introduce higher levels of compressive stress into cemented carbide mining inserts, a high energy tumbling (HET) method may be used. HET tumbling may typically be performed as follows: using an ERBA 120 with a disc size of about 600 mm, running at about 180 RPM if the tumbling operation is performed without media or with media that is larger in size than the insert being tumbled, or about 240 RPM if the media used is smaller in size than the insert being tumbled; using a Rösler tumbling machine with a disc size of about 350 mm, running at about 280 RPM if the tumbling operation is performed without media or with media that is larger in size than the insert being tumbled, or about 320 RPM if the media used is smaller in size than the insert being tumbled. Typically, the parts are tumbled for at least 40-80 minutes.

[0064] In one embodiment, the high energy tumbling treatment is carried out at an elevated temperature above 100°C, preferably at an elevated temperature above 200°C, more preferably at an elevated temperature between 200°C and 450°C. An advantage of the elevated tumbling temperature is that the toughness of the carbides is increased, so collisions do not lead to defects such as microcracks, macrocracks or chipping. The combination of higher levels of compressive stress and reduced collision defects will improve the fatigue resistance and fracture toughness of the mining blade, thereby increasing the life of the blade. A further advantage of this method is that blade geometries that were previously prone to excessive damage to the corners and therefore had low productivity, such as those with a small bottom radius, can now be tumbled without causing edge damage. This opens up the possibility of developing mining blade products with different geometries that were not previously suitable for tumbling. The method also makes it possible to use cemented carbide compositions that were previously too brittle for mining applications. The ability to introduce higher levels of compressive stress means that the toughness of the mining blade is increased to an acceptable level, so mining blades with higher hardness can be used, which is beneficial for increasing the wear resistance of the mining blade.

[0065] In one embodiment, the pressing pressure used to pre-press the first powder is less than the pressing pressure used to press the second powder onto the first portion of the green body. Advantageously, this results in reduced cracking.

[0066] In one embodiment, prior to the sintering step, a liquid dispersion or slurry comprising a grain refiner compound containing a grain refiner and carbon and / or nitrogen, and a grain growth promoter as carbon is applied to at least a portion of the surface of the green body of the cemented carbide, wherein the grain refiner compound and the grain growth promoter are both present in an amount of 0.1 to 100 mg / cm 2 An amount is provided to the one or more surfaces.

[0067] The grain refiner compound is a carbide, mixed carbide, carbonitride or nitride, and the grain refiner compound and the grain growth promoter are provided on the surface of the compact by first providing a compact and then providing the grain refiner compound and the grain growth promoter on at least a portion of the surface of the compact, the grain refiner compound and the grain growth promoter being provided by applying to the compact as separate or combined liquid dispersions or slurries, with a weight ratio of grain refiner compound to grain growth promoter being from about 0.05 to about 50. The compact is sintered after the grain refiner compound and the grain growth promoter have been applied to the surface of the compact prior to the surface hardening treatment.

[0068] The grain refiner compound is preferably a carbide or nitride of chromium or vanadium.Further details on the method of applying the grain refiner compound and the grain growth promoter to the surface of the cemented carbide compact can be found in EP2355948B1.

[0069] In one embodiment, at least a metal oxide or metal carbonate is applied to at least one location of the surface of the green cemented carbide insert prior to sintering. Advantageously, this redistributes the binder in a tailored and most advantageous manner, thereby providing optimal functionality to the cemented carbide mining insert while introducing higher levels of compressive stress into the cemented carbide mining insert.

[0070] In one embodiment of the method, the binder puller, which is a metal oxide or metal carbonate, is selected from Cr2O3, MnO, MnO2, MoO2, Fe-oxide, NiO, NbO2, V2O3, MnCO3, FeCO3, CoCO3, NiCO3, CuCO3 or Ag2CO3. Alternatively, a metal may also be applied to the surface of the green cemented carbide mining insert, which metal will form an oxide when heated during the sintering step. The choice of the metal oxide or metal carbonate will affect the properties of the cemented carbide after sintering, such as strain hardening, heat resistance and / or corrosion resistance, and may be selected to best suit the desired application. If the equivalent metal oxide is toxic and the metal carbonate is non-toxic, the metal carbonate is selected. In this method, there is a high degree of freedom as to where the binder puller is applied, for example, it may be applied in the wear zone of the cemented carbide tool or away from the wear zone, depending on whether the metal in the oxide or carbonate improves the wear resistance of the cemented carbide.

[0071] In one embodiment of the method, the binder pulling agent is Cr2O3. The advantage of using Cr2O3 as the binder pulling agent is that a chromium-rich surface layer will be formed which has an enhanced response to the tumbling process. Therefore, higher compressive stresses will be introduced and the wear properties of the cemented carbide mining insert will be improved. Cr3O2 contributes to grain refinement, so a reduced grain size is measured on the side of the insert to which Cr3O2 is applied.

[0072] In one embodiment, the tool used for the pre-punching is curved. Advantageously, this compacts the corners, thereby avoiding the creation of sharp corners, which helps prevent the first portion of the green body from collapsing after the pre-punching.

[0073] According to one embodiment, the cemented carbide insert is mounted in a rock drill bit body of a top hammer (TH) device or a down-the-hole (DTH) drilling device or a rotary drilling device or a cutting disk device. The rotary drilling device may be an oil and gas rotary cutter device. The invention also relates to a rock drilling or cutting device, in particular a top hammer device, or a down-the-hole drilling device, or a rotary drilling device, or a cutting disk device, and the use of a cemented carbide insert according to the invention in such a device.

[0074] Another aspect of the present disclosure relates to the use of a cemented carbide mining insert as described above or below for rock drilling or oil and gas drilling.

[0075] Example

[0076] Example 1 (Invention)

[0077] Inserts were pressed from two WC / Co powders, both containing 6 wt% Co and 0.6 wt% Cr in the binder, but with different WC grain sizes in the green body, 1.5 μm in the upper half and 1.0 μm in the lower half (about 50% / 50% by volume of powder). The green body was symmetrical around the central axis and about 17 mm high and 12 mm wide. The 20 kg load Vickers hardness (HV20) of the sintered body of the pure top powder was 1559, and the HV20 of the pure sintered bottom powder was 1781. The Co-magnetic values ​​of the two powders were similar.

[0078] After sintering, the sintered body was cut in half, and the Co content and HV20 were measured along the center of the polished sample. The results are shown in Figure 1 along with a line showing the hardness of the reference material. Figure 3 middle.

[0079] The Co content was also measured along the central axis using wavelength dispersive X-ray spectroscopy (WDS) with a microprobe. The results are shown in Figure 4 middle.

[0080] Figure 3 and Figure 4 Both clearly show that during sintering the original distribution of Co in the green body is largely retained intact, resulting in a sintered body with two distinct parts in terms of hardness, with a sharp change in hardness at the interface between the two powders.

[0081] Example 2 (Comparison):

[0082] Inserts were pressed from two WC / Co powders, both containing 6 wt% Co in the binder but without alloying elements. As in Example 1, the WC grain sizes were different in the green body, 1.3 μm in the upper half and 2.3 μm in the lower half (powder volume ratio was about 50% / 50%). The size and shape of the green body were the same as in Example 1. The 20 kg load Vickers hardness (HV20) of the sintered body of the pure top powder was 1573, and the HV20 of the pure sintered bottom powder was 1439. The Co-magnetic values ​​of the two powders were also similar.

[0083] After sintering, the sintered body was cut in half, and the Co content and HV20 were measured along the center of the polished sample. The results are shown in Figure 1 along with a line showing the hardness of the reference material. Figure 5 middle.

[0084] Also along the central axis, the Co content was measured with a microprobe using wavelength dispersive X-ray spectroscopy (WDS). The results are shown in Figure 6 middle.

[0085] from Figure 5 and Figure 6 It can be clearly seen in Figure 1 that the Co (same weight percentage in both powders) which was uniformly distributed in the green body redistributes during sintering. This results in a uniform hardness in the sintered body, reaching values ​​between those of the sintered reference material.

[0086] Example 3 (Comparison):

[0087] Inserts were pressed from two WC / Co powders, both with 6 wt% Co, 0.6 wt% Cr in the top powder, but no alloying elements in the binder for the bottom powder. The WC grain size was different in the green body, 1.5 μm in the top half and 1.1 μm in the bottom half, with a powder volume ratio of about 50% / 50%. The size and shape of the green body were the same as in Examples 1 and 2. The 20 kg load Vickers hardness (HV20) of the sintered body of the pure top powder was 1559, and the HV20 of the pure sintered bottom powder was 1640.

[0088] After sintering, the sintered body was cut in half, and the Co content and HV20 were measured along the center of the polished sample. The results are shown in Figure 1 along with a line showing the hardness of the reference material. Figure 7 middle.

[0089] Also along the central axis, the Co content was measured with a microprobe using wavelength dispersive X-ray spectroscopy (WDS). The results are shown in Figure 8 middle.

[0090] from Figure 7 and Figure 8It can be clearly seen in Figure 1 that the Co (same weight percentage in both powders) which was uniformly distributed in the green body redistributed during sintering. This resulted in an irregular hardness distribution with softening in the top part and increasing hardness in the bottom part.

[0091] It should be understood that any one or more of the embodiments may be combined together.

Claims

1. A sintered carbide insert (2) for use in mining or cutting applications, comprising: A first zone (4), the first zone comprising: 3-18 wt% binder phase; Any unavoidable impurities; The balance is tungsten carbide having an average grain size between 0.5 and 20 μm; and A second zone (6), the second zone comprising: The same amount of a binder phase as the first zone (4) within + / - 3 wt % thereof; Any unavoidable impurities; The balance of tungsten carbide having an average grain size between 0.5 and 20 μm; wherein the first region (4) and the second region (6) are adjacent to each other; wherein the average grain size of WC in the first zone (4) is different from the average grain size of WC in the second zone (6); Features include: The binder phase in both the first zone (4) and the second zone (6) comprises between 2-15 wt% Cr measured as a fraction of the total binder content.

2. The insert (2) according to claim 1, further comprising one or more cemented carbides selected from TiC, TaC and / or NbC in the first zone (4) and / or the second zone (6).

3. The insert (2) according to claim 1 or 2, wherein the difference in average grain size between the first zone (4) and the second zone (6) is >0.5 µm.

4. The insert according to any one of the preceding claims, wherein the difference between the binder phase content in the first zone (4) and the second zone (6) is less than 1.5 wt.-%.

5. The blade (2) according to any one of the preceding claims, wherein the blade (2) comprises a base (8); a working tip (10); a core (12) and a longitudinal centre axis (14).

6. The insert (2) according to claim 5, wherein the first zone (4) is positioned at the working tip (10) and the second zone (6) is positioned at the base (8), and wherein the WC average grain size of the first zone (4) is between 1-2 µm and the WC average grain size of the second zone (6) is between 3-16 µm.

7. The insert (2) according to claim 5, wherein the first zone (4) is positioned at the working tip (10) and the second zone (6) is positioned at the base (8), and wherein the WC average grain size of the first zone (4) is between 3-16 µm and the WC average grain size of the second zone (6) is between 1-2 µm.

8. A blade according to any one of the preceding claims, wherein The difference in hardness between the first zone 4 and the second zone 6 is >50 HV20 when measured according to ISO EN6507 3:2005.

9. The insert (2) according to any one of the preceding claims, wherein an interface (16) between the first region (4) and the second region (6) is substantially straight.

10. The insert (2) according to any one of claims 1-8, wherein the interface (16) between the first region (4) and the second region (6) is dome-shaped.

11. A method for manufacturing a cemented carbide insert according to any one of claims 1 to 10, the method comprising the following steps: a) providing a first powder comprising between 3-18 wt% binder, 2-15 wt% Cr measured as a fraction of the total binder content, and any unavoidable impurities, and the balance a WC hard phase having an average grain size of 0.5-20 μm; b) pre-pressing the first powder to provide a first portion of a green body; c) providing a second powder, the second powder comprising between 3-18 wt % of a binder, 2-15 wt % of Cr and any unavoidable impurities, and the balance of a WC hard phase having an average grain size of 0.5-20 μm; d) pressing the second powder onto the first portion of the green body to provide a second portion of the green body; c) sintering the entire green compact to form the sintered cemented carbide insert (2) having the first region (4) and the second region (6).

12. The method according to claim 11, wherein: After sintering, the cemented carbide insert (2) is tumbled.

13. The method according to claim 11 or claim 12, wherein a pressing pressure for pre-pressing the first powder is less than a pressing pressure for pressing the second powder onto the first portion of the green body.

Citation Information

Patent Citations

  • Cemented carbide body and method

    EP2355948B1